Implementation of the DMAIC Approach for Quality Improvement in the Garment Industry: A case study - Pham, Cao Văn; Tu, Hữu Công; Vo, Trọng Cang (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
This study aims to implement the Lean Six Sigma method on Jean products in a garment company in Vietnam to reduce the defect rate. The methodology is based on the Define, Measure, Analyze, Improve, and Control (DMAIC) approach. In addition, the paper also uses other tools, such as the SIPOC model, Pareto chart, fishbone diagram, and control chart, to propose ideas to enhance factory quality. After more than 1 month, the results show that applying quality management tools based on the DMAIC process has decreased the defect rate from 4.40% to 1.06%.